Outcome of treatment with concurrent whole brain radiotherapy and Temozolomide in brain metastasis (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Brain metastasis represents the most common form of intracranial tumor and causes significant morbidity and mortality in cancer patients. This prospective study was carried out at Radiation Oncology Department, Combined Military Hospital Dhaka from January 2010 to December 2012. The concurrent chemotherapy and radiotherapy have shown better outcome and improved the quality of life. Objectives: To evaluate the efficacy and toxicity of concurrent treatment with whole brain radiotherapy (WBRT) and temozolomide (TMZ) in patients with brain metastasis. Methods: Sixty patients with multiple brain metastases were enrolled and received WBRT with 30 Gray (Gy) in ten fractions with concurrent TMZ (75mg/m2/day) for ten days. Results: Remarkable symptomatic relief occurred in eighteen (72%) patients of headache, nine (60%) patients of altered mental status, thirteen (76.5%) of vomiting, ten (71.4%) of seizure, eleven (68.7%) of altered sensation, seven (58.3%) of focal weakness and two (40%) of visual change. In relation to objective response four (6.7%) patients had complete response, twenty three (38.3%) patients had partial response while twenty one (35%) had stable disease and twelve (20%) had progressive disease. The overall response rate was 45%. The most frequent toxicities included anorexia in twenty one (35%), nausea in eighteen (30%), vomiting in ten (16.6%), lethargy in seventeen (28%), anemia in eight (13.3%) and neutropenia in thirteen (21.6%) cases. 64 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Conclusion: The concurrent treatment with whole brain radiotherapy (WBRT) and temozolomide (TMZ) in patients with brain metastasis is well tolerated with an encouraging response. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22927 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014